Effect of a transtheoretical model-based intervention and motivational interviewing on hyperphosphatemia management via telehealth (TMT program) among hemodialysis patients during the COVID-19 pandemic - Arrom Thongsunti; Chatchawan Silpakit; Thanapoom Rattananupong; Wonngarm Kittanamongkolchai; Wonngarm Kittanamongkolchai; Wonngarm Kittanamongkolchai; Warangkana Sumethpimolchai; Vitool Lohsoonthorn (Frontiers Media S.A., 2024)
BackgroundHyperphosphatemia poses a significant risk for cardiovascular diseases and mortality in hemodialysis patients. Non-adherence to phosphate binders and a low-phosphate diet behavior contribute to this issue. Leveraging psychological and behavior change theories has proven effective in addressing many health risks. During the COVID-19 pandemic, face-to-face communication was limited, and telehealth served as a bridge to address healthcare gaps. This study aimed to determine the effect of a transtheoretical model-based intervention and motivational interviewing on hyperphosphatemia management via telehealth (TMT program) among hemodialysis patients during the COVID-19 pandemic.MethodA two-arm parallel randomized controlled trial with assessors blinding involved 80 participants who were stratified block-randomized into either the TMT program group (n = 40) or the control group (Usual care; n = 40). Linear regression was used to compare the two groups on serum phosphorus levels, knowledge of hyperphosphatemia management, and dietary consumption behavior at the 24-week endpoint. The readiness to change (stage of change), self-efficacy, and phosphate binder adherence were assessed using Fisher's test.ResultThe TMT program demonstrated a significant reduction in serum phosphorus levels compared to usual care (mean difference = −1.03, 95% CI = −1.77, −0.29). Additionally, improvement in dietary consumption behavior related to phosphorus-containing foods was also observed (mean difference = 13.48, 95% CI = 8.41, 18.57). Positive effects emerged in the readiness to change (p < 0.001), self-efficacy in the appropriate use of phosphate binders (p = 0.025), and adherence to phosphate binders (p = 0.001) at the 24-week endpoint. However, groups did not differ in knowledge of hyperphosphatemia management (mean difference = 7.02, 95% CI = −1.03, 15.07).ConclusionThe study demonstrated that the TMT program has positive effects on reducing serum phosphorus levels, providing a hyperphosphatemia management strategy for ESRD patients undergoing hemodialysis via telehealth.Clinical trial registrationTCTR20230628003, https://www.thaiclinicaltrials.org.